74 MULTICENTER VALIDATION OF CORRECTION FACTORS FOR CEREBROSPINAL FLUID LABORATORY VALUES IN YOUNG INFANTS WITH A TRAUMATIC LUMBAR PUNCTURE. (19th August 2020) - Rogers, Sarah; Gravel, Jocelyn; Anderson, Gregory; Papenburg, Jesse; Quach, Caroline; Burstein, Brett
Abstract: Background: The evaluation of fever among infants in the first months of life remains one of the most common problems in pediatric healthcare. Approximately 10% harbor potentially life-threatening infections including bacterial meningitis, frequently necessitating invasive cerebrospinal fluid (CSF) testing by lumbar puncture (LP). LPs are often traumatic leading to uninterpretable results and consequently, broad-spectrum antibiotic exposure and prolonged hospitalization. Several strategies have been proposed to identify low-risk infants with traumatic LPs, including recently-derived correction factors, however studies validating the safety and diagnostic utility of such approaches are lacking. Objectives: To evaluate the test characteristics and misclassification rates of recently described ratio-based correction methods for the interpretation of CSF results among young infants with traumatic LPs. Design/Methods: We undertook a multicenter cohort study of infants aged ≤60 days with a traumatic LP performed at two urban tertiary Pediatric hospitals from 2006 to 2018. Traumatic LPs were defined as CSF specimens with ≥10, 000 RBCs/mm 3, and for infants aged ≤28 days and 29-60 days, pleocytosis was defined as ≥20 and ≥10 WBC/mm 3, respectively, and abnormal protein ≥1.15 and ≥0.89 g/L, respectively. CSF WBCs and protein were adjusted downward for traumatic LPs using RBC ratio-based correction methods (newly derived 877:1, commonly used 500 and 1000:1, peripheral RBC:WBC ratio, and newly derived 1000 RBCs:0.011g/L protein). Descriptive statistics are presented with sensitivity, specificity, and negative predictive values of unadjusted and adjusted CSF for predicting culture-proven bacterial meningitis. Results: Of 4, 912 LPs meeting inclusion criteria, 437 (8.9%) were traumatic, among which 4 (0.9%) were positive for bacterial meningitis. Compared to uncorrected CSF WBC counts, both 877 and 1000 correction factors classified fewer infants with pleocytosis (38.0% and 42.6% vs 81.7%). These correction factors both maintained 100% sensitivity and 100% negative predictive value, and performed with greater specificity for bacterial meningitis than the uncorrected WBC count (62.6% and 58.0% vs 18.5%). No infants with bacterial meningitis were misclassified using either 877 or 1000:1 correction factors. CSF 500:1 and peripheral RBC:WBC correction ratios performed with the lowest sensitivity and negative predictive values and both misclassified 1 infant with bacterial meningitis. Corrected CSF protein outperformed uncorrected protein in specificity (66.8% vs 33.9%), but did not add diagnostic value when used in combination with WBC correction ratios. Conclusion: Correction of the CSF WBC count substantially reduced the number of infants classified with CSF pleocytosis. The newly-derived 877:1 correction factor performed with the best test characteristics, safely reclassifying nearly half of all infants with a traumatic LP. It may be appropriate to use a correction factor in the evaluation of CSF cell counts in traumatic LPs in order to more effectively risk-stratify febrile young infants, reduce antibiotic exposure and admission duration.